The Apple Autophagy-Related Gene MdATG9 Confers Tolerance to Low Nitrogen in Transgenic Apple Callus - Huo, Liuqing; Guo, Zijian; Zhang, Zhijun; Jia, Xin; Sun, Yiming; Sun, Xun; Wang, Ping; Gong, Xiaoqing; Ma, Fengwang (Frontiers in Plant Science, 2020)
Autophagy is an efficient degradation system for maintaining cellular homeostasis when plants are under environmental stress. ATG9 is the only integral membrane protein within the core ATG machinery that provides a membrane source for autophagosome formation. In this study, we isolated a new apple autophagy gene, MdATG9, from Malus domestica. The analysis of its sequence, subcellular localization, promoter cis-elements, and expression patterns revealed the potential function of MdATG9 in the autophagy process in response to abiotic stressors. Overexpression of MdATG9 in apple callus conferred enhanced tolerance to nitrogen depletion stress. During the treatment, other important MdATGs were expressed at higher levels in transgenic callus than in the wild type, indicating higher autophagic activity in the transgenic lines. Furthermore, more free amino acids and increased sucrose levels were found in MdATG9-overexpression apple callus compared with the wild type in response to nitrogen starvation. These data suggest that MdATG9 is an important autophagy gene, possessing a conserved function in the apple autophagy process, and it plays an important role in the metabolic mechanism in response to nutrient starvation in apple plants.